Implementasi Projek Penguatan Profil Pelajar Pancasila Melalui Tema Bhinneka Tunggal Ika pada Peserta Didik Kelas VII SMP Negeri 6 Singkawang - Niko Juliansyah; Bistari Bistari; Shilmy Purnama; Sulistyarini Sulistyarini; Amrazi zakso (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to explore: (1) the planning process in implementing the Strengthening the Profile of Pancasila Students (P5) project through the theme Bhinneka Tunggal Ika among Class VII students at SMP Negeri 6 Singkawang; (2) the implementation of the P5 project with that theme in Class VII; and (3) the challenges encountered and solutions applied during the project's execution. The research adopts a qualitative approach with a case study method. The subjects include the principal, the vice principal for curriculum affairs, the head of the facilitator team, and students. Informants were selected using purposive sampling, ensuring data was obtained from participants chosen based on specific criteria to ensure relevance and accuracy. Data collection methods involved in-depth interviews, direct observations, and documentation. The data were analyzed using the Miles and Huberman model, consisting of three stages: data reduction, data display, and conclusion drawing. The findings reveal that: (1) prior to the implementation of the P5 project, careful planning is required by the school; (2) the project is carried out in several phases, namely orientation, contextualization, real action, reflection, and follow-up; and (3) challenges in implementing the P5 project include a lack of student participation and engagement, transportation issues due to mechanical failure, and a mismatch between the chosen theme and the project dimensions. The proposed solutions involve using student-led discussion methods, providing better-maintained transportation, and selecting more specific and consistent themes, dimensions, and topics to ensure successful project implementation.